SURGICAL TREATMENT OF A PATIENT WITH MULTIPLE FRACTURES OF THE THORACIC AND LUMBAR VERTEBRAE ASSOCIATED WITH HAJDU – CHENEY SYNDROME - Vissarionov, S. V.; Filippova, A. N.; Zhurbitskaia, M. V.; Khusainov, N. O.; Belyanchikov, S. M. (Khirurgii︠a︡ pozvonochnika = Spine surgery, 2019)
A clinical case of surgical and multimodal conservative treatment of an 11-year-old female patient with Hajdu – Cheney syndrome with multiple vertebral fractures in the thoracic and lumbar spine is presented. The main and significant manifestations of this syndrome are osteoporosis and acroosteolysis. After the injury, the child underwent correction of posttraumatic spinal deformity and stabilization of spinal motion segments by a placement of multi-anchor instrumentation through a posterior approach. The long-term postoperative period was characterized by the absence of bone block formation, development of distal junctional kyphosis and scoliotic deformity, which required additional surgical intervention in the amount of elongation of instrumentation and correction of the developed curvature. The paper describes in detail the clinical manifestations of the syndrome, the results of surgical treatment, and clinical and radiological characteristics.